2010
DOI: 10.1063/1.3521397
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a fast gas analyzer based on Raman scattering for the analysis of synthesis gas

Abstract: A sensor system for fast analysis of synthesis gas (mixtures of CO and H(2)) is proposed and characterized. The system is based on spontaneous Raman scattering, which enables simultaneous concentration measurements of all relevant species. For typical synthesis gas applications, this system has to face large variations of temperature and pressure. In addition, strong fluctuations in mixture composition may occur, which lead to rather inconvenient signal intensities. In this paper, we describe a low resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Related information to spectral soft modeling can be found elsewhere. [2,4,[33][34][35][36] The used contour-fit algorithm determines the relative species concentration in volume percent fully automatically. For the quantitative gas analysis with the evaluation technique described here, three main conditions must be fulfilled within the operating range of the sensor system:…”
Section: Data Evaluation and Calibration Proceduresmentioning
confidence: 99%
“…Related information to spectral soft modeling can be found elsewhere. [2,4,[33][34][35][36] The used contour-fit algorithm determines the relative species concentration in volume percent fully automatically. For the quantitative gas analysis with the evaluation technique described here, three main conditions must be fulfilled within the operating range of the sensor system:…”
Section: Data Evaluation and Calibration Proceduresmentioning
confidence: 99%
“…Two further much weaker bands at 812 cm −1 and 1032 cm −1 were also observed (see Figure S1 in the supplementary information), corresponding to the transitions S 0 (2) (J = 2 → 4) and S 0 (3) (J = 3 → 5) respectively. 25,36 Higher rotational levels were not observed because these levels are not significantly populated at room temperature. 3,36 From the spectrum of the evacuated tube it can be seen that sampling through the glass wall of the NMR tube does not complicate the spectrum in this region, except with a broad glass signal which can be easily removed with baseline correction (see Figure S1 for examples of nonbaseline correct spectra).…”
Section: Raman Spectra Of Hydrogen Gasmentioning
confidence: 99%
“…25,36 Higher rotational levels were not observed because these levels are not significantly populated at room temperature. 3,36 From the spectrum of the evacuated tube it can be seen that sampling through the glass wall of the NMR tube does not complicate the spectrum in this region, except with a broad glass signal which can be easily removed with baseline correction (see Figure S1 for examples of nonbaseline correct spectra). As expected, the spectrum from the pH 2 enriched sample had a much greater proportion of signal from the rotational band corresponding to the pH 2 isomer, compared to the spectrum from the nH 2 sample.…”
Section: Raman Spectra Of Hydrogen Gasmentioning
confidence: 99%
“…For syngas containing carbon monoxide, this range would need to be extended to ~2300 cm −1 , which is possible in a straightforward manner. Eichmann et al [68] substituted carbon monoxide by carbon dioxide for safety reasons, as CO is a highly toxic substance and can be harmful even at low concentration [69]. Therefore, syngas applications require high safety standards and gas leakage must be detected as early as possible; hence the need for highly sensitive analytical methods.…”
Section: Alternative Gaseous Fuels and Special Applicationsmentioning
confidence: 99%
“…For example, synthesis gas (also known as syngas), which represents mixtures mainly comprising of carbon monoxide and hydrogen, were analyzed by Raman techniques. Eichmann et al [68] carried out a systematic investigation of the pressure and temperature influence on the Raman spectra of carbon dioxide/hydrogen mixtures in order to develop an approach for determining the composition of syngas. Moreover, they discussed the suitability of different spectral ranges used for data evaluation and concluded that the fingerprint region from 300 to 1600 cm −1 provides the best accuracy.…”
Section: Alternative Gaseous Fuels and Special Applicationsmentioning
confidence: 99%